Connections between air pollution, traffic and respiratory health - Diya Peng (Universitas Lampung, 2022)
Air pollution increases the likelihood of developing a variety of health issues, particularly in the field of respiration. Involuntary exposure to traffic-related air pollution affects humans from fetal development to death. Nitrogen dioxide, sulfur dioxide, carbon monoxide, benzene, ozone, particulate matter 10 (PM10), lead, arsenic, cadmium, nickel, benzopyrene, and particulate matter 2.5 (PM2.5) are among the lung-damaging substances found in air pollutants. Determining the causal relationship between various major road pollutants and the human respiratory system is a difficult task. In general, it can be concluded that traffic-related pollutants will induce an inflammatory response that will progress based on the variation of humans exposed. The concept of oxidative stress resulting from traffic-related pollutants has also begun to receive extensive research. This gives hope for assisting the human anti-oxidant system in combating the increasingly difficult-to-avoid threat of air pollution.